Effectiveness of Virtual Reality on Fatigue and Life Quality in Geriatric Patients at Kasih Nursing Home Cirebon, Indonesia - Gani, Hadrian; Gunawan, Hendry; Gunawan, Irene (GHMJ (Global Health Management Journal), 2024)
Background: Fatigue is a significant challenge for geriatric patients, often leading to vulnerability and a poor quality of life. Virtual reality can potentially serve as a therapeutic intervention for fatigue and quality of life by positively influencing geriatric patients' motor and cognitive functions. Aims: To analyze the effectiveness of virtual reality training on fatigue and quality of life in geriatric patients at Kasih Nursing Home Cirebon, Indonesia. Methods: The research type was a quasi-experimental design with a pre-test, post-test, and nonequivalent group design. Sampling utilized non-probability sampling techniques, specifically total sampling divided into two groups. The intervention group received five treatment sessions over five weeks, each session lasting 15 minutes and conducted on the same days apart. Data was collected using the Fatigue Severity Scale and the World Health Organization Quality of Life-BREF. Data analysis employed paired t-tests, independent t-tests, and N-Gain scores. Results: The results of the paired t-test for the control group showed a non-significant difference in fatigue (p = 0.363 > 0.05). In contrast, the intervention group showed significant improvements in fatigue (p < 0.001) and quality of life (p = 0.049). The independent t-test revealed no significant differences between groups in pre-test scores. However, post-test scores showed significant differences between groups for fatigue (p = 0.048) and quality of life (p = 0.004). The N-Gain Score test indicated that the virtual reality motor cognitive intervention was effective in reducing fatigue (83.96%) but had a limited impact on quality of life (28.32%). Conclusion: Virtual reality training is effective against fatigue, however, while there was a significant increase in quality of life after the virtual reality intervention; virtual reality was not significantly effective in improving the overall quality of life of geriatric patients. Received: 24 September 2024  |  Reviewed: 16 October 2024  |  Revised: 30 November 2024  |  Accepted: 11 December 2024.